THE PROTECTION AND PEOPLE'S RIGHTS DISABILITY AS CONSTITUTIONAL RIGHTS THROUGH THE PUBLIC SERVICE REGULATIONS - Dedi Putra (Universitas Muhammadiyah Metro, 2017)
The respect, protection, and fulfillment of the rights of persons with disabilities is an obligation of the state as stipulated in Article 42 of Law No. 39 of 1999 on human rights. Persons with disabilities has been experiencing a lot of discrimination that has not met the right of persons with disabilities. Disability should have the same opportunity in the effort to develop itself. Fulfillment of the rights of persons with disabilities is still considered as a social problem that the new policy with its rights is social security, social assistance, and increase social welfare. Protection and fulfillment of the rights of persons with disabilities can be done by providing and facilitating access to public services. The right to obtain public services should also be reserved for disabled people. The right to obtain public services for disabled people should be seen as a constitutional right. The regulation of public services should provide protection and fulfillment of the constitutional rights of the disabled in obtaining public services. This paper will discuss the law enforcement ideal in strengthening the rights of persons with disabilities as constitutional rights through fair regulation of public services. This paper uses a method normative approach to legislation.